GOVERNING IMPACT AND FEEDBACK IN WORK OF STATE POWER BODIES - Gennadiy I. Koval'tsev (Вестник Российского экономического университета имени Г. В. Плеханова)
The article discloses numerous forms of interaction and communication accomplishing through types of their activity, i.e. governing impact and feedback. The author widens the implication of the notion ‘Feedback’ by attracting institutions of civil society and business community for participation in shaping state decisions (governing impact) and control of their realization. It is the most important direction of work effectiveness of state power bodies. The types of governing impact of the entity on the object being governed were researched. The author subdivided them into normative-legal interference and normative-legal regulation. It was shown that without enhancing forms and methods of state regulation and interference with wide application of feedback it is impossible to shape effective state decisions necessary for progressive social and economic development of the country.